Fetal haemoglobin and alpha 1 microglobulin as biochemical markers in predicting preeclampsia in late first trimester and early second trimester of pregnancy - Vijaya, S.; Mahalakshmi, M.; Inbapriyanka, I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia is a multi system disorder with placenta as the organ of origin and maternal endothelium being the organ of target. According to recent studies, the cell free haemoglobin induces oxidative stress mediated damage to the blood placenta barrier with consequently elevated levels of HbF in maternal blood. Alpha 1 microglobulin is an endogenous protein with antioxidant property, present in elevated levels in maternal blood in response to oxidative stress. This fact forms the basis for our study. The objective of the present study was to establish association between high levels of fetal hemoglobin and alpha 1 microglobulin in plasma of pregnant women between 10 to 16 weeks of gestational age and subsequent development of preeclampsia. Methods: This was a prospective cohort study undertaken in the Department of Obstetrics and Gynaecology, ISO -KGH, between December 2016 to November 2017. A total of 100 pregnant women were included in the study after getting informed written consent. Both primigravida and multigravida, belonging to age group of 20 to 35 years (singleton/ multiple) between 10 to 16 weeks GA and with BMI between 16 to 35 kg/m2 were included in the study. A woman with Diabetes mellitus, Hypertension, Renal disease, Epilepsy and Vascular disorders were excluded from the study. Results: The cut off value for alpha 1 microglobulin was 1.86ng/ml and the cut off value of fetal haemoglobin was 1.92ng/ml above which the pregnant women develop preeclampsia. Conclusions: Higher values of fetal hemoglobin and alpha 1 microglobulin in pregnant women between 10 to 16 weeks gestational age positively correlates with development of preeclampsia in those women.